2017
DOI: 10.1021/acscatal.7b01371
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Nitrate Reduction over Indium-Decorated Palladium Nanoparticle Catalysts

Abstract: Nitrate (NO3 −) is an ubiquitous groundwater contaminant and is detrimental to human health. Bimetallic palladium-based catalysts have been found to be promising for treating nitrate (and nitrite, NO2 −) contaminated waters. Those containing indium (In) are unusually active, but the mechanistic explanation for catalyst performance remains largely unproven. We report that In deposited on Pd nanoparticles (NPs) (“In-on-Pd NPs”) shows room-temperature nitrate catalytic reduction activity that varies with volcano-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
166
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(171 citation statements)
references
References 79 publications
5
166
0
Order By: Relevance
“…The Gibbs free energy changes for the NO 3 À reduction progress can be obtained by the following Equations (1)- (7), where *r epresents the active site: [19][20][21][22][23][24] NO 3 1 ðIÞþ* ! NO 3 * ð1Þ…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…The Gibbs free energy changes for the NO 3 À reduction progress can be obtained by the following Equations (1)- (7), where *r epresents the active site: [19][20][21][22][23][24] NO 3 1 ðIÞþ* ! NO 3 * ð1Þ…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…Multiple "bimetallic" catalysts for this transformation exist; each consists of a mixture of two metal particles, at least one of which is made of a scarce and expensive noble metal-Ru, Pd, or Pt-which decreases their potential utility and prevents their large-scale deployment. 18,19,20,21,22 A few reports with base metals exist. 23,24,25,26,27 Compounding this problem, some nitrate reduction methods suffer from limited activity and/or poor yields.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations and discussions have been performed to clarify the reaction intermediates. [20][21][22] They have demonstrated that nitrite ions are reduced on the surface of the noble metal to adsorbed NO as the key intermediate in the generation of nitrogen (N 2 ) and ammonium (NH 4 + ). Two different pathways for the reduction of NO to NH 4 + have been proposed: NO dissociation and NO hydrogenation.…”
Section: Introductionmentioning
confidence: 99%